2014
DOI: 10.1515/bot-2014-0005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of repopulation techniques for the giant kelp Macrocystis pyrifera (Laminariales)

Abstract: In Chile, the brown alga Macrocystis pyrifera has been subject to strong harvesting pressure, resulting in severe reduction of natural beds, and a threat to the sustainability of the resource. Repopulation is a possible means for the recovery of overexploited natural populations of M. pyrifera. In this study, we determined density (ind. cm-2), length (mm) and biomass (g) of M. pyrifera sporophytes sown on three types of substrata (ceramic plates, pot scrubbers, clam shells). In laboratory experiments, sporoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…The techniques used for the transplant of juveniles included planting seedlings on different substrates, such as boulders, pottery, or mesh, and fastening them with elastic bands (Figure 4E, F) or glue (cyanoacrylate) to later place them in subtidal environments (Westermeier, 2013;Westermeier et al, 2014). Vaśquez et al (2014) also used M. pyrifera seedlings on three different substrates: pottery, tuffy pads, and clam shells; laboratory and field experiments showed that a greater biomass of seedlings attached to clam shells (60% more biomass than other substrates), and they concluded that the installation of substrate units with seaweed seedlings could be an option for the recovery of exploited M. pyrifera subtidal kelp forests.…”
Section: Restocking From Seeding or Transplants Of Juvenile Sporophytesmentioning
confidence: 99%
See 1 more Smart Citation
“…The techniques used for the transplant of juveniles included planting seedlings on different substrates, such as boulders, pottery, or mesh, and fastening them with elastic bands (Figure 4E, F) or glue (cyanoacrylate) to later place them in subtidal environments (Westermeier, 2013;Westermeier et al, 2014). Vaśquez et al (2014) also used M. pyrifera seedlings on three different substrates: pottery, tuffy pads, and clam shells; laboratory and field experiments showed that a greater biomass of seedlings attached to clam shells (60% more biomass than other substrates), and they concluded that the installation of substrate units with seaweed seedlings could be an option for the recovery of exploited M. pyrifera subtidal kelp forests.…”
Section: Restocking From Seeding or Transplants Of Juvenile Sporophytesmentioning
confidence: 99%
“…For example, no great changes attributable to global drivers have been reported for kelp forest ecosystems located off the South American coast (Perúand Chile), probably owing to the effects of the Humboldt Current, which has prevented water warming over recent decades (Seabra et al, 2019;Smale, 2020). However, in this region, particularly along the Chilean coast, threats are associated with the extraction and potential direct overexploitation of large extensions of seaweeds along the entire coast, mainly kelp forest species as Lessonia trabeculata, Lessonia spicata, Lessonia berteroana and Macrocystis pyrifera (Vaśquez et al, 2012;Vaśquez et al, 2014). The consequences of this practice could be devastating for these ecosystems, and it should thus be regulated adequately to avoid their collapse (Maŕquez and Vaśquez, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…-transplants directly to pre-installed plastic mesh Campbell et al, 2014. -substrates hosting individuals to preinstalled plastic mesh Vásquez et al, 2014. Deployment of substrates hosting laboratory-reared individuals:…”
Section: Restoration Technique Examples Referencesmentioning
confidence: 99%
“…Vegetative transplantation uses either young or old plants and either threads, gravel bags, or concrete blocks [321][322][323]. Vegetative transplantation is used to grow small sporophytes (<1 cm in height) on artificial substrata in the laboratory; the substrata are then placed in the field [330] or used to transplant much larger juvenile and adult sporophytes that are less sensitive to bottom conditions. Vegetative transplantation is very laborintensive; many plants are harvested, transported, and individually attached to the bottom.…”
Section: Vegetative Transplantationmentioning
confidence: 99%
“…Young plants are much easier to transplant than adults and can be attached to the stumps (i.e., holdfasts plus short sections of stipes) of understory kelps after the upper portions have been removed [206]. Juvenile kelps were transplanted in California during the 1970s and 1980s, and recruitment was successful near the southern limit in Baja California after the mass kelp disappearance during the El Niño event of 1997-1998 [301,330]. Similar approaches have been used in Mexico [206], Japan [333], and Chile [330].…”
Section: Vegetative Transplantationmentioning
confidence: 99%